Assessing the Implementation of Workplace Health Programs Outside of Controlled Environments - Walker, E. (Methods of Information in Medicine, 2000)
The study explored the implementation of workplace health programmes in 14 NHS Trusts (hospitals). It sought to identify different approaches to implementation and measures that could be used to guide future development. The study comprised inter-related elements examining the process of implementing workplace health and the impact on staff. An innovative action research approach was applied to the evaluation. The aims of the evaluation were to generate activity and learning within the organisations which was sustainable (long term) and transferable outside the study organisations. The study is described in terms of the multiple methods and the ways in which these have been brought together in the analysis. The approach has been informed by a shift from an individualistic perspective towards one which sees the health of workers within the broader context of organisational development and management. The research identified a number of dilemmas for workplace health with its focus on the health of the individual. A typology was developed which describes different approaches to workplace health and their impact on sustaining such initiatives. It suggests that for workplace health to be successful it must address the organisational context as well as individual staff needs. Results from a survey of staff in the 14 trusts seems to demonstrate an association between the approaches, described in the typology, and an impact on staff. Workplace health programmes need to shift towards approaches where the individual’s health is seen within the wider context of the organisation.
Keywords: Workplace Health; Research; Evaluation; Organisational Health, Typology; Case-Studies; Health at Work; Settings